Hexafluoroisopropanol as solvent and promotor in the Paal-Knorr synthesis of N-substituted diaryl pyrroles - Schirmacher, Robert H. E.; Rösch, Daniel; Thomas, Franziska (Tetrahedron, 2021)
An additive-free synthesis of challenging N-substituted aryl pyrroles from the often poorly soluble corresponding 1,4-diketones by means of the Paal-Knorr pyrrole synthesis is reported, which makes use of the unique properties of 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) as a solvent and reaction promotor. Our procedure offers simple execution and purification as well as easy scale-up and can be applied in the Paal-Knorr synthesis of a large number of structurally diverse pyrroles including the synthetically challenging tetra- and penta-substituted pyrroles in moderate to excellent yields. HFIP can also be used as solvent in the Paal-Knorr synthesis of furans and thiophenes; however, the solvent effect is more pronounced in synthesis of pyrroles.
Gesehen am 04.08.2021